Transient nature of fast relaxation in metallic glass. (15th October 2022) - Zella, Leo; Moon, Jaeyun; Keffer, David; Egami, Takeshi
Abstract: Metallic glasses exhibit fast mechanical relaxations at temperatures well below the glass transition, one of which shows little variation with temperature known as nearly constant loss (NCL). Despite the important implications of this phenomenon to deformation, the origin of the relaxation is unclear. Through molecular dynamics simulations of a model metallic glass, C u 64.5 Z r 35.5, we implement molecular dynamics dynamical mechanical spectroscopy (MD-DMS) with system stress decomposed into atomic-level stresses to identify the group of atoms responsible for NCL. This work demonstrates that NCL relaxation is due to transient groups of atoms that revert to the typical atomic-level viscoelastic behavior over picosecond timescales. They are homogenously distributed throughout the glass and have no outstanding features, rather than having defect-like local structure as previously reported. Graphical abstract: Image, graphical abstract